Accounting Students' Perception of Green Accounting: Implications on Financial Performance and Corporate Sustainability - Muliani; Baiq Dinda Puspita Ayu; Nukman (EAJ (Economic and Accounting Journal), 2025)
This study aims to explore the perception of accounting students toward green accounting and its implications for financial performance and corporate sustainability. The method used is a qualitative method with a phenomenological approach to understanding student perceptions in depth as 60 students in the accounting program semester 4 in Bumigora University. The data collection technique was carried out through in-depth interviews with students of the accounting study program. The instrument used is a semi-structured interview guide that allows for further exploration flexibility. The study results show that accounting students have a progressive view of green accounting, corporate sustainability issues, respecting corporate social responsibility and environmental impact. These findings emphasize the importance for companies to implement green accounting and pay attention to the environmental impact of the company's operational activities so as not to damage the environment which will have a positive impact on the company's sustainability and financial performance in the long term.